Conflitos socioambientais no contexto da Política Nacional de Resíduos Sólidos: implantação da logística reversa do plástico - Morais, Karine Tavares (2015)
This research aims to identify the challenges present in the implementation of shared esponsibility among the principal actors of the National Solid Waste Policy (PNRS), with emphasis on the industrial sector of plastic, because this large waste generator. The goal is to restore the historical processing of PNRS the Federal Congress to understand how the plastics industry is responding to legal requirements on the importance of managing one of the most abundant waste on the environment. The aim is to identify and characterize environmental conflicts embedded in the legal obligation of PNRS, given the economic interests of the industry and, in particular, such as streamline conflicts or hamper sectoral agreements between government and business representative bodies. The research is based on desk research, in which it was possible to identify the plastics sector companies resist the responsibility to bear the weight of the Reverse Logistics without the consideration of the public sector. It appears from the central role of the Ministry of Environment in mediating between economic agents and the representative institutions of the segments involved with the effective implementation of selective collection system which depends on the recycling industry in Brazil and Reverse Logistics in the country.